Perancangan User Interface Dan User Experience Website Reservasi Rima Villa Ciwidey Dengan Metode Design Thinkings - Leli Safitri; Nadiyah Dalilah; Murtiwiyati Murtiwiyati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Villas are one of the important lodging entities in the tourism sector, where villas are needed as a place to rest. A good villa cannot be separated from good service. The purpose of this writing is to improve user experience and user efficiency in the villa reservation process. The Design Thinking method is used as a creative approach in designing user experiences that meet user needs and expectations. The stages of Design Thinking, starting from understanding the problem to implementing the solution. In the UI/UX design process, data is collected through observation, interviews and analysis of user needs. The results are used to identify areas of improvement and guide prototype development. This writing contributes to the development of the UI/UX of the Rima Villa Ciwidey reservation website by applying a Design Thinking approach and utilizing SUS metrics to measure the quality of user experience. The use of the System Usability Scale (SUS) is used as a tool for measuring UI/UX performance, with a resulting value of 70.05. These results show a good level of user satisfaction and are also included in the prototype design which is user friendly, that is, easy for the user to use.